Education and technology in sciences First International Congress, CISETC 2019, Arequipa, Peru, December 10-12, 2019, Revised selected papers /: First International Congress, CISETC 2019, Arequipa, Peru, December 10-12, 2019, Revised selected papers. (2020) - Unknown
No abstract available